Inefficacy of alcohol‐based hand rub on mites in a patient with hyperkeratotic scabies. (1st March 2015) - Cinotti, E.; Perrot, J. L.; Labeille, B.; Maguet, H.; Couzan, C.; Flori, P.; Cambazard, F.
Summary: Background: The Wold Health Organization is strongly promoting alcohol‐based hand rubs to interrupt transmission of pathogens within the healthcare environment, and in some hospitals they are being recommended in cases of scabies. However, there are no studies that demonstrate the efficacy of such hand rubs against scabies. Aim: To evaluate the viability of Sarcoptes scabiei after the application of various topical antiseptics used for hand hygiene, and the effect of hand washing on the number of parasites present on the skin surface of a patient with scabies. Methods: We applied three different topical antiseptics (two alcohol‐based and one povidone–iodine‐based) to the skin of one hand that was affected by scabies, and took a skin scraping of each area to evaluate the viability of the mites over time. A skin scraping of a control area without antiseptic application was also taken. We also tested the antiseptics directly on the mites. Statistical comparison between the percentages of vital mites in the different samples was assessed using the χ 2 test. We also captured a dermoscopic image of the other hand before and after hand washing to count the number of parasites on the skin surface. Results: Topical antiseptics did not reduce the number of living mites compared with control skin, and hand washing did not reduce the number of parasites on the skin surface. Conclusions: Application of topical antiseptics does not reduce the viability of S. scabiei, and is therefore unable to prevent the transmission of scabies. The usefulness of hand washing in preventing transmission of scabies to new subjects remains to be investigated.